ARTIFICIAL INTELLIGENCE IN BANKING: THE FUTURE OF DIGITAL FINANCIAL - Loso Judijanto; Desi Yuniarti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Artificial Intelligence (AI) has become a transformative force in the banking and digital financial services industry, fundamentally changing the way financial institutions operate and interact with customers. The research method used was literature review. The results show that AI has great potential to revolutionize the banking industry, but also presents challenges that need to be overcome, thus the importance of balancing innovation and regulation, as well as the need for an ethical approach in the development and implementation of AI solutions in the financial sector.